The Effect of Digital Technology on the Quality of Health Services in Health Centers - Dedeh Husnaniyah; Samuel Hadjo (Professional Evidence-based Research and Advances in Wellness and Treatment, 2026)
The application of digital technology in health services has become increasingly important as public demand for fast, accurate, and transparent services continues to grow. Puskesmas, as first-level healthcare facilities, are required to adapt to technological developments to improve service quality. However, challenges such as service delays, administrative inefficiencies, and limited use of digital systems still persist. This study aims to analyze the effect of digital technology implementation on the quality of health services at Andalas Padang Health Center. The research employed a quantitative method with an associative approach. The population consisted of all patients receiving services at the health center, with a sample of 100 outpatient respondents selected through accidental sampling. All respondents had utilized digital-based services such as electronic registration and administration. Data were collected using questionnaires and analyzed using simple linear regression with statistical software. The results showed that digital technology implementation has a positive and significant effect on service quality, with a regression coefficient of 0.652 and a significance value of 0.000 (<0.05). The coefficient of determination (R²) was 0.425, indicating that 42.5% of service quality variation is explained by digital technology, while the rest is influenced by other factors. In conclusion, optimizing digital technology improves healthcare service quality.